2019
DOI: 10.1080/2162402x.2019.1677139
|View full text |Cite
|
Sign up to set email alerts
|

Patients with melanoma of unknown primary show better outcome under immune checkpoint inhibitor therapy than patients with known primary: preliminary results

Abstract: Background: Melanoma of unknown primary (MUP) is an uncommon clinical subtype of melanoma of known primary (MKP).Objectives: We aimed to compare treatment outcomes of MUP and MKP patients who had undergone therapy with immune checkpoint inhibitors (ICPI).Methods: We studied 41 metastatic melanoma patients (32 with MKP and 9 with MUP) with an indication for ICPI.Results: Clinical characteristics such as age, gender, stage of disease, etc., did not significantly differ (P < .05) between MUP and MKP patients. 20/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…BRAF mutations rate in MUPs appears similar to MKPs; however, for MUPs the rate for V600K seems higher than the rate for MKPs (24). Melanomas with the V600K mutation are characterized by a lower dependence on the activation of the ERK pathway and greater use of alternative pathways; against these melanomas they have a higher mutational load and respond better to immunotherapy; this would concretely explain the better response to immunotherapy and the worse response to BRAFi/ MEKi of the MUPs (25)(26)(27). The strengths of our study include the diagnosis of MUP based on Das Gupta's criteria (2), the sample size (one of the largest in MUP literature), the evaluation of Balch's staging proposal, and the evaluation of systemic treatments.…”
Section: Discussionmentioning
confidence: 89%
“…BRAF mutations rate in MUPs appears similar to MKPs; however, for MUPs the rate for V600K seems higher than the rate for MKPs (24). Melanomas with the V600K mutation are characterized by a lower dependence on the activation of the ERK pathway and greater use of alternative pathways; against these melanomas they have a higher mutational load and respond better to immunotherapy; this would concretely explain the better response to immunotherapy and the worse response to BRAFi/ MEKi of the MUPs (25)(26)(27). The strengths of our study include the diagnosis of MUP based on Das Gupta's criteria (2), the sample size (one of the largest in MUP literature), the evaluation of Balch's staging proposal, and the evaluation of systemic treatments.…”
Section: Discussionmentioning
confidence: 89%
“…Despite the lack of response in uveal melanoma patients, we noted high response rates in patients diagnosed with melanomas of unknown primary, with four of the five patients (80%) with unknown primaries showing clinical benefit. This is a promising result for this patient cohort as several studies have found conflicting data regarding their responses to ICIs 16,17 . In addition, we noted several responses in difficult to treat metastatic sites, including the adrenal gland 18 .…”
Section: Discussionmentioning
confidence: 68%
“…The observed lower median survival may be explained by the fact that patients who were not treated with novel therapies (or not treated at all) were also included. Another recent small pilot study showed different results in 41 patients treated with ICI [ 41 ]. The patient population was small and included a relatively high number of patients with MUP (22%) with comparable baseline characteristics as patients with MKP.…”
Section: Resultsmentioning
confidence: 99%